INTEREST RATE CHANGES AND ISLAMIC STOCK RETURN WITH WAVELETS: THE CASE OF INDONESIA - Zulaikha, Siti (STAI BHAKTI PERSADA BANDUNG, 2018)
In a global economy, shocks affect many financial sectors including stock market through the discount factor of the cash flow model. As in the conventional stock market where global shocks play a significant role in influencing stock prices, it also occurs in the Islamic stocks. This paper investigates the linkage between interest rate and stock returns for Indonesia with the sample period from January 2005 to December 2012 in the time-frequency domain by using a number of cross-wavelet tools. The results reveal that the similar response of the Islamic and conventional equity finance to the global shock. In turn, the result depicts that the Islamic equity market is also sensitive to the monetary tools used in the conventional system. The results have useful implications for policy makers in the face of a global financial crisis to prevent the steep fall of stock market price by increasing or decreasing the interest rate. In other words, since interest rate changes have an impact in the stock market, harmonisation of monetary policies mainly in developed countries can contribute to a decrease in the contagion potential on the stock markets